Upcycled recycled polyethylene polypropylene blends

By adding low melting point C2-C8 plastics and random propylene copolymers to the polyethylene-polypropylene blend, the weight ratio and melt flow rate of the composition are optimized, and the polyethylene-polypropylene in the prior art is solved. The problem of insufficient rigidity and impact strength of the blend achieves high economic and market attractive material effects.

CN116134086BActive Publication Date: 2024-12-24北欧化工公司
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202180059111.8
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Priority Date
2020-07-30
Filing Date
2021-07-29
Publication Date
2024-12-24
Estimated Expiration
2041-07-29

AI Technical Summary

Technical Problem

Existing polyethylene-polypropylene blends have limitations in improving rigidity and impact strength, especially the use of expensive block copolymers or high amounts of random heterophase copolymers, resulting in increased cost and limited economics, and It is difficult to achieve business appeal.

Method used

Using a composition based on a polyethylene-polypropylene composition, the weight ratio and melt flow rate are optimized to improve the pull of the composition by adding a low melting point C2-C8 plastic and random propylene copolymer as a compatibilizer. Modulus and impact strength reduce density and cost.

Benefits of technology

A polyethylene-polypropylene blend with high rigidity and appropriate impact strength is achieved under relatively small amounts of compatibilizers, reducing production costs and improving the economicality and market attractiveness of the materials.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0004113633490000131
    Figure BDA0004113633490000131
  • Figure BDA0004113633490000132
    Figure BDA0004113633490000132
  • Figure BDA0004113633490000141
    Figure BDA0004113633490000141
Patent Text Reader

Abstract

The present invention relates to an upgraded polypropylene-polyethylene blend comprising a random polypropylene copolymer and an ethylene-based plastomer.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to an upgraded recycled blend comprising primarily polyethylene and polypropylene. Background Art

[0002] In the field of polyolefins, it is necessary to use recycled materials from a variety of sources. However, the available recycled streams are all affected by limited mechanical properties and cannot achieve commercially attractive end uses. Various expensive reinforcing polymers have been proposed to upgrade the recycled streams, resulting in less economical regeneration. Therefore, the market for recycled blends is currently very limited and any upgraded components must be as cheap as possible. In blends mainly comprising polyethylene and polypropylene, it is relatively easy to obtain higher impact strength by adding an elastomer that acts as a compatibilizer (such as traditional ethylene-propylene rubber or EPDM). WO2015 / 169690A1 teaches the addition of a multiphase ethylene-propylene copolymer (HECO) comprising an ethylene-octene-copolymer, which is commercially available from Borealis Plastomers (NL) under the trade name Or purchased from DOW Chemical Corp (USA) under the trade name or available from ENI SpA (IT). However, the use of any heterogeneous ethylene-propylene copolymer (HECO) does not necessarily produce good results, especially in terms of stiffness. It is generally believed that the limited stiffness can only be overcome by using plastomers with block copolymer properties (such as Dow Infuse OBC or Intune OBC plastomers provided by Dow Chemical). For example, INTUNE TM Polypropylene-based OBC (PP-OBC) is designed as a compatibilizer rather than an elastomer. They contain a propylene-rich block compatible with polypropylene and an ethylene-rich block compatible with polyethylene. It can be easily understood that block copolymers introduce the option of making certain domains have higher rigidity, thereby increasing rigidity as a whole. However, the disadvantage of plastomers (which are easily measured by NMR and further reflected by melting temperature) with block copolymer properties is that they are relatively expensive. In addition to using OBC materials, it is further known to add random heterophasic copolymers (RAHECO), including propylene ethylene random copolymer matrix and ethylene propylene rubber as dispersed phase. However, the amount of RAHECO required is generally quite high. In addition, many end uses do not require excessive impact properties. It is understandable that the waste problem involving polymers requires compatibilizers that allow polymers to be reused in very high amounts in the final product. Summary of the invention

[0003] There is an urgent need for an ingenious compatibilizer that allows providing an upgraded polypropylene-polyethylene blend having sufficiently high stiffness and suitably high impact strength with a relatively small amount of compatibilizer.

[0004] The present invention provides within this scope

[0005] A polyethylene-polypropylene composition having a melt flow rate of 5.0 to 12.0 g / 10 min, wherein the polyethylene-polypropylene composition can be obtained by blending:

[0006] a) 52 to 92 wt%, preferably 65 to 91 wt%, more preferably 70 to 90 wt%, most preferably 71 to 89 wt%, based on the total weight of the polyethylene-polypropylene composition, of a blend (A), the blend (A) comprising:

[0007] A-1) polypropylene, and

[0008] A-2) Polyethylene,

[0009] wherein the weight ratio of polypropylene to polyethylene is from 19:1 to 7:3, and

[0010] wherein blend (A) is a recycled material recovered from waste plastic materials derived from post-consumer waste and / or industrial waste; and

[0011] b) 5 to 35 wt%, preferably 5 to 22 wt%, more preferably 6 to 18 wt%, most preferably 7 to 17 wt%, based on the total weight of the polyethylene-polypropylene composition, of a compatibilizer (B), the compatibilizer (B) being selected from C2C4 plastomers, C2C6 plastomers, C2C8 plastomers and mixtures thereof, the compatibilizer (B) having:

[0012] - a DSC melting point (ISO 11357) below 75°C, preferably below 73°C, more preferably below 60°C, most preferably between 38°C and 60°C;

[0013] - MFR2 (ISO 1133, 2.16 kg load at 190°C) of 1.5 g / 10 min or less, preferably 1.0 g / 10 min or less, most preferably 0.1 to 0.5 g / 10 min; and

[0014] -885kg / m 3 Density below 875 kg / m 3 Below, most preferably 858 to 867 kg / m 3 density (ISO1183), and

[0015] c) 3 to 12 wt%, preferably 4 to 12 wt%, and most preferably 4 to 11 wt%, relative to the total weight of the polyethylene-polypropylene composition, of a random polypropylene copolymer having an MFR2 (ISO 1133, 2.16 kg load at 230°C) of less than 1.0 g / 10 min; and

[0016] d) 0 to 1.0 wt% of a stabilizer or a stabilizer blend, relative to the total weight of the polyethylene-polypropylene composition,

[0017] Thus, the polyethylene-polypropylene composition has a tensile modulus (ISO 527-2) of at least 600 MPa, preferably at least 700 MPa, more preferably at least 800 MPa and most preferably from 850 to 1000 MPa tensile modulus.

[0018] The present invention further provides an article comprising, preferably consisting of, the polyethylene-polypropylene composition of the present invention.

[0019] The present invention also relates to a process for providing the polyethylene-polypropylene composition of the invention as defined above, wherein the process comprises the following steps:

[0020] a) providing a blend (A) in an amount of 52 to 92 wt%, preferably 65 to 91 wt%, more preferably 70 to 90 wt%, most preferably 71 to 89 wt%, based on the total weight of the polyethylene-polypropylene composition, wherein the blend (A) comprises polypropylene and polyethylene in a ratio of 19:1 to 7:3,

[0021] b) providing a compatibilizer (B) in an amount of 5 to 35 wt%, preferably 5 to 22 wt%, more preferably 6 to 18 wt%, and most preferably 7 to 17 wt%, based on the total weight of the polyethylene-polypropylene composition, wherein the compatibilizer (B) is a C2C4 plastomer, a C2C6 plastomer, a C2C8 plastomer and a mixture thereof, and the compatibilizer (B) has:

[0022] - a DSC melting point (ISO 11357) below 75°C, preferably below 73°C, more preferably below 60°C, most preferably between 38°C and 60°C;

[0023] - MFR2 (ISO 1133, 2.16 kg load at 190°C) of 1.5 g / 10 min or less, preferably 1.0 g / 10 min or less, most preferably 0.1 to 0.5 g / 10 min; and

[0024] -885kg / m 3 Density below 875 kg / m 3 Below, most preferably 858 to 867 kg / m 3 Density (ISO1183);

[0025] c) providing a random polypropylene copolymer in an amount of 3 to 12 wt%, preferably 4 to 12 wt%, and most preferably 4 to 11 wt%, relative to the total weight of the polyethylene-polypropylene composition, wherein the random polypropylene copolymer has an MFR2 (ISO 1133, 2.16 kg load at 230° C.) of less than 1.0 g / 10 min;

[0026] d) melting and mixing the blend in the presence of 0 to 1.0 wt% of a stabilizer or a mixture of stabilizers, relative to the total weight of the polyethylene-polypropylene composition, and

[0027] d) Optional granulation.

[0028] On the other hand, the present invention provides

[0029] The compatibilizer (B) is used together with the random polypropylene copolymer to improve the impact-rigidity balance of the blend (A). The compatibilizer (B) is a C2C8 plastomer, the MFR2 (ISO1133, 2.16 kg load at 230°C) of the random polypropylene copolymer is less than 1.0 g / 10 min, and the compatibilizer (B) has:

[0030] - a DSC melting point (ISO 11357) below 75°C, preferably below 73°C, more preferably below 60°C, most preferably between 38°C and 60°C;

[0031] - MFR2 (ISO 1133, 2.16 kg load at 190°C) of 1.5 g / 10 min or less, preferably 1.0 g / 10 min or less, most preferably 0.1 to 0.5 g / 10 min; and

[0032] -885kg / m 3 Density below 875 kg / m 3 Below, most preferably 858 to 867 kg / m 3 Density (ISO1183),

[0033] The blend (A) comprises:

[0034] A-1) polypropylene, and

[0035] A-2) Polyethylene,

[0036] wherein the weight ratio of polypropylene to polyethylene is from 19:1 to 7:3, and

[0037] wherein blend (A) is a recycled material recovered from waste plastic materials derived from post-consumer waste and / or industrial waste; and

[0038] Blend (A) is present in an amount of 52 to 92 wt%, preferably 65 to 91 wt%, more preferably 70 to 90 wt%, most preferably 71 to 89 wt% relative to the final polyethylene-polypropylene composition, and

[0039] The compatibilizer (B) is present in an amount of 5 to 35 wt%, preferably 5 to 22 wt%, more preferably 6 to 18 wt%, most preferably 7 to 17 wt% relative to the final polyethylene-polypropylene composition, and

[0040] The random polypropylene copolymer is present in an amount of 3 to 12 wt%, preferably 4 to 12 wt%, most preferably 4 to 11 wt%, relative to the final polyethylene-polypropylene composition, and the MFR2 (ISO 1133, 2.16 kg load at 230° C.) of the random polypropylene copolymer is below 1.0 g / 10 min.

[0041] definition

[0042] Unless otherwise defined, all technical and scientific terms used herein have the same meaning as those generally understood by those of ordinary skill in the art to which the present invention belongs. Although any method and material similar or equivalent to that described herein can be used to test the present invention in practice, preferred materials and methods are described herein. When describing and claiming the present invention, the following terms will be used according to the definitions set forth below. Unless otherwise expressly stated, the use of the term "a, an" etc. refers to more than one.

[0043] Plastomers are copolymers composed of units derived from ethylene and 1-butene, ethylene and 1-hexene, or ethylene and 1-octene. Plastomers mean that the copolymers have rubber-like properties.

[0044] "Upgrading" refers to improving one or more properties, such as Charpy notched impact and / or stiffness as reflected, for example, by tensile modulus.

[0045] For the purposes of the present invention, "improving the impact-stiffness balance" shall mean a Charpy notched impact strength (1eA) (non-instrumented at +23°C, ISO 179-1) of at least 14 kJ / m 2 , while the tensile modulus in MPa (ISO527-2) is at least 850 to 1000 MPa.

[0046] For the purposes of this specification, the term "recycled waste" or "recycled material" is used to refer to materials recovered from both post-consumer waste and industrial waste, as opposed to virgin polymers. Post-consumer waste refers to items that have completed at least the first use cycle (or life cycle), that is, have reached their first purpose; while industrial waste refers to manufacturing waste, which usually does not reach the hands of consumers. The term "virgin" refers to newly produced materials and / or items that have not been recycled before first use. Virgin materials and recycled materials can be easily distinguished based on the presence or absence of contaminants such as limonene and / or fatty acids and / or paper and / or wood. Polypropylene-polyethylene blends can also be distinguished from their sources by the presence of polystyrene and / or polyamide. Residual content refers to the content above the detection limit. Many different types of polyethylene or polypropylene can be present in "recycled material". The ratio of polypropylene (A-1) to polyethylene + polyethylene copolymer (A-2) was experimentally determined by calibration using isotactic polypropylene (iPP) and high-density polyethylene (HDPE). A polymer blend is a mixture of two or more polymer components. Typically, a blend can be prepared by mixing two or more polymer components. A "compatibilizer" is a substance in polymer chemistry that can be added to a polymer blend with limited miscibility to increase its stability. A "polypropylene-polyethylene blend" refers to a composition containing polypropylene and polyethylene, which also includes polypropylene copolymers and polyethylene copolymers. Since the content of polypropylene and the content of polyethylene cannot be directly determined, the weight ratio of polypropylene (A-1) to polyethylene (A-2) is 19:1 to 7:3, which refers to an equivalent ratio determined by calibration of iPP and HDPE and infrared spectroscopy. The stabilizer is selected from an antioxidant and / or a light stabilizer.

[0047] Compatibilizer (B)

[0048] The compatibilizer (B) of the present invention is a plastomer selected from C2C4 plastomer, C2C6 plastomer, C2C8 plastomer and a mixture thereof, wherein the plastomer has:

[0049] - a DSC melting point (ISO 11357) below 75°C, preferably below 73°C, more preferably below 60°C, most preferably between 38°C and 60°C;

[0050] - MFR2 (ISO 1133, 2.16 kg load at 190°C) of 1.5 g / 10 min or less, preferably 1.0 g / 10 min or less, most preferably 0.1 to 0.5 g / 10 min; and

[0051] -885kg / m 3 Density below 875 kg / m 3 Below, most preferably 858 to 867 kg / m 3 Density (ISO1183).

[0052] Most preferably, the compatibilizer (B) of the present invention is a C2C8 plastomer, wherein the plastomer has:

[0053] - a DSC melting point (ISO 11357) below 75°C, preferably below 73°C, more preferably below 60°C, most preferably between 38°C and 60°C;

[0054] - MFR2 (ISO 1133, 2.16 kg load at 190°C) of 1.5 g / 10 min or less, preferably 1.0 g / 10 min or less, most preferably 0.1 to 0.5 g / 10 min; and

[0055] -885kg / m 3 Density below 875 kg / m 3 Below, most preferably 858 to 867 kg / m 3 Density (ISO1183).

[0056] The compatibilizer (and the preferred compatibilizers described below) are commercially available. The melting point excludes the presence of blocky characteristics. The DSC melting point of the compatibilizer (B) of the present invention is preferably below 73°C, more preferably below 60°C (ISO11357). On the other hand, the density of the compatibilizer (B) of the present invention is preferably 875 kg / m 3 The following (ISO1183): C2C8 plastomers are particularly preferred.

[0057] When compatibilizer (B) is used without component (C) as described below, the impact strength is increased compared to blend (A). It should be understood that it is possible but not really necessary to use an amount of compatibilizer (B) above 23 wt%, since the goal is to dump as high an amount of blend (A) as possible in the resulting composition. Furthermore, it is not necessary to have too high an impact strength value.

[0058] Random Polypropylene Copolymer (C)

[0059] The MFR2 (ISO 1133, 2.16 kg load at 230°C) of the random polypropylene copolymer (C) of the present invention is below 1.0 g / 10 min. Most preferably, the MFR2 (ISO 1133, 2.16 kg load at 230°C) of the random polypropylene copolymer (C) of the present invention is from 0.1 to 0.5 g / 10 min. The low melt flow rate ensures the introduction of sufficient polymer chains of considerable length. The rather low melt flow rate of the random polypropylene copolymer (C) contributes to impact resistance and rigidity. The random polypropylene copolymer (C) of the present invention is preferably a propylene-ethylene copolymer, i.e. the copolymer consists only of units derived from propylene and ethylene. The random polypropylene copolymer (C) of the present invention is commercially available.

[0060] The tensile modulus of the random polypropylene of the present invention is preferably at least 950 MPa (ISO 527-2).

[0061] In another aspect of the present invention, the ethylene content of the random polypropylene of the present invention is preferably 3.0 to 6.0 wt%.

[0062] Preferably, the random polypropylene having an ethylene content of 3.0 to 6.0 wt% of the present invention consists of units derived from propylene and ethylene only.

[0063] Most preferably, the random polypropylene of the present invention has an ethylene content of 3.0 to 6.0 wt%, consists of units derived from propylene and ethylene only and has a tensile modulus of at least 950 MPa (ISO 527-2).

[0064] Polypropylene-polyethylene blends (A)

[0065] The polypropylene-polyethylene blend (A) of the present invention preferably has one or more of the following properties:

[0066] a) a limonene content of 0.1 ppm to 100 ppm, preferably 0.1 ppm to 50 ppm, more preferably 0.1 ppm to 20 ppm, most preferably 0.1 ppm to 5 ppm, determined using solid phase microextraction (HS-SPME-GC-MS);

[0067] b) 0.1 to 100 ppm fatty acid content, determined using solid phase microextraction (HS-SPME-GC-MS);

[0068] c) a polyamide content of 0.05 to 5.0 wt %, as determined by IR;

[0069] d) 0.05 to 6.0 wt% polystyrene content, determined by IR.

[0070] Preferably, the polypropylene-polyethylene blend (A) of the present invention is a recycled material, more preferably originating from household waste. In a specific and particularly preferred embodiment, the blend (A) originates from plastic waste in the ocean.

[0071] The polypropylene-polyethylene blend (A) of the present invention comprises:

[0072] (A-1) polypropylene, and

[0073] (A-2) polyethylene,

[0074] The weight ratio of polypropylene (A-1) to polyethylene (A-2) is 19:1 to 7:3.

[0075] It should be understood that the polypropylene-polyethylene blend (A) may vary widely in composition, i.e. may comprise polypropylene homopolymer, polypropylene copolymer, polyethylene homopolymer and polyethylene copolymer. Since the polypropylene content and polyethylene content cannot be directly determined, the weight ratio of polypropylene (A-1) to polyethylene (A-2) of 19:1 to 7:3 is an equivalent ratio determined by calibration with iPP and HDPE.

[0076] Generally, the polypropylene-polyethylene blend (A) of the present invention may have one or more of the following:

[0077] - residual PET, determined as described in the experimental section;

[0078] - residual talc and chalk content, as described in the experimental part;

[0079] - Residual metal content (determined by X-ray fluorescence (XRF));

[0080] - Paper residue, as described in the experimental section;

[0081] - Wood residue, as described in the experimental section;

[0082] - Total free fatty acid content ranged from 0.1 to 100 ppm, determined using headspace solid phase microextraction (HS-SPME-GC-MS).

[0083] Preferably, components a) to d) as described herein add up to 100 wt%. DETAILED DESCRIPTION

[0084] The present invention particularly relates to a polyethylene-polypropylene composition having a melt flow rate of 5.0 to 12.0 g / 10 min, which can be obtained by mixing:

[0085] a) 71 to 89 wt% of a blend (A), the blend (A) comprising:

[0086] A-1) polypropylene, and

[0087] A-2) Polyethylene,

[0088] wherein the weight ratio of polypropylene to polyethylene is from 19:1 to 7:3, and

[0089] wherein blend (A) is a recycled material recovered from waste plastic materials derived from post-consumer waste and / or industrial waste; and

[0090] b) 7 to 17 wt% of a compatibilizer (B), the compatibilizer (B) being a C2C8 plastomer having:

[0091] - a DSC melting point (ISO 11357) below 75°C, preferably below 73°C, more preferably below 60°C, and most preferably between 38°C and 60°C;

[0092] - MFR2 (ISO 1133, 2.16 kg load at 190°C) of 1.5 g / 10 min or less, preferably 1.0 g / 10 min or less, most preferably 0.1 to 0.5 g / 10 min; and

[0093] -885kg / m 3 Density below 875 kg / m 3 Below, most preferably 858 to 867 kg / m 3 density (ISO1183), and

[0094] c) 4 to 11 wt% of a random polypropylene copolymer having an MFR2 (ISO 1133, 230°C, 2.16 kg load) of 1.0 g / 10 min or less; and

[0095] d) 0 to 1.0 wt% of a stabilizer or a stabilizer mixture,

[0096] The polyethylene-polypropylene composition thus has a tensile modulus between 850 and 1000 MPa.

[0097] Experimental Section

[0098] The following examples are included to illustrate specific aspects and embodiments of the present invention as described in the claims. However, it should be understood by those skilled in the art that the following description is only exemplary and should not be regarded as limiting the present invention in any way.

[0099] Test Method

[0100] a) Amount of iPP, polystyrene, polyethylene (and copolymers containing ethylene) and polyamide-6

[0101] iPP and HDPE were mixed with iPP, PS and PA6 to establish different standards for different calibration curves. To quantify the content of foreign polymers, a Bruker Vertex 70 FTIR spectrometer was used to record infrared spectra in the solid state. Films were prepared using a compression molding device at 190 °C with a clamping force of 4-6 MPa. The film thickness for the iPP and HDPE calibration standards was 300 μm, while for the quantification of iPP, PS and PA6, a film thickness of 50-100 μm was used. Standard transmission FTIR spectroscopy was used with a spectral range of 4000-400 cm -1 , aperture is 6mm, spectral resolution is 2cm -1 , 16 background scans, 16 spectral scans, interferogram zero fill factor of 32, and Norton Beer strong apodization.

[0102] Measured 1167cm in iPP -1 The absorption band at 240 nm was detected and the iPP content was quantified according to the calibration curve (absorption / thickness in cm2 versus iPP content in wt%).

[0103] Measured at 1601cm -1 (PS) and 3300cm -1 The absorption band at (PA6) is determined and the PS and PA6 contents are quantified according to the calibration curve (absorption in cm / thickness vs. PS and PA contents in wt%). The content of polyethylene and ethylene-containing copolymers is obtained by subtracting (iPP+PS+PA6) from 100, taking into account the content of non-polymer impurities determined in the following method. The analysis is performed in duplicate.

[0104] b) Tensile modulus and tensile strain at break

[0105] Measured according to ISO 527-2 (test speed = cross / crosshead speed; for tensile modulus evaluation: at 1 mm / min (0.05-0.25% measured extensometer), at 23°C using injection molded specimens 1B (dog bone shape, 4 mm thick) prepared as described in EN ISO 1873-2, when reaching 0.25%, at 50 mm / min until fracture. The specimens are measured after a conditioning time of 96 hours at 23°C.

[0106] c) Impact strength

[0107] According to ISO179-1 eA, 80×10×4 mm at +23°C, 0°C and -20°C 3Charpy notched impact strength of injection molded specimens (prepared according to EN ISO 1873-2). The specimens were measured after a conditioning time of 96 hours at 23°C.

[0108] e) Comonomer content

[0109] Poly(propylene-co-ethylene)-ethylene content-IR spectrum

[0110] Quantitative infrared (IR) spectroscopy was used to quantify the ethylene content of poly(ethylene-co-propylene) copolymers by calibration to the primary method. 13 Calibration was facilitated by internal non-commercial calibration standards of known ethylene content determined by C solution-state nuclear magnetic resonance (NMR) spectroscopy. The calibration procedure was performed in the usual manner well documented in the literature. The calibration set consisted of 38 calibration standards with ethylene contents ranging from 0.2 to 75.0 wt%, manufactured at small or full scale under various conditions. The calibration set was selected to reflect typical copolymer species encountered by the final quantitative infrared spectroscopy method.

[0111] Quantitative IR spectra were recorded in the solid state using a Bruker Vertex 70 FTIR spectrometer. Spectra were recorded on 300 μm thick 25×25 mm square films prepared by compression molding at 180-210° C. and 4-6 MPa. For samples with very high ethylene content (>50 mol%), 100 μm thick films were used. Standard transmission FTIR spectroscopy was used in the spectral range of 5000-500 cm -1 , aperture is 6mm, spectral resolution is 2cm -1 , 16 background scans, 16 spectral scans, interferogram zero filling factor of 64, and Blackmann-Harris 3-phase apodization. Use the corresponding (CH2) >2 Structural unit (integration method G, limits 762 and 694 cm -1 ) of 730 and 720cm -1 (A Q ) was used to quantify the total area of ​​CH2 rocking deformation at 4650 and 4007 cm. The quantitative bands were normalized to the bands corresponding to the CH structural units (integration method G, limits 4650 and 4007 cm -1 ) of 4323cm -1 The CH band area at (AR) is then calculated from the normalized absorbance (A) using a secondary calibration curve. Q / A R) predicts the ethylene content in weight percent. The calibration curve has been previously constructed by ordinary least squares (OLS) regression of normalized absorbance and major comonomer content (measured on the calibration set).

[0112] Poly(propylene-co-ethylene)-ethylene content- 13 C NMR spectroscopy

[0113] The Bruker Avance III 400 NMR spectrometer was used to analyze 1 H and 13 C was operated at 400.15 and 100.62 MHz to record quantitative 13 C{ 1 H}NMR spectroscopy. 13 All spectra were recorded at 125°C using a C optimized 10 mm extended temperature probe head and nitrogen was used for all pneumatics. Approximately 200 mg of material was dissolved in 3 mL of 1,2-tetrachloroethane-d2 (TCE-d2) along with chromium(III) acetylacetonate (Cr(acac)3) to give a 65 mM relaxation agent solution in the solvent (Singh, G., Kothari, A., Gupta, V., Polymer Testing 28 5 (2009), 475).

[0114] To ensure that the solution is homogeneous, the NMR tube is further heated in a rotary furnace for at least 1 hour after initial sample preparation in a heating block. After being inserted into the magnet, the tube rotates at 10 Hz. This setting was chosen primarily to obtain the high resolution and quantification required for accurate ethylene content quantification. A standard single pulse excitation without NOE was used, using an optimized top cone angle, 1 s cycle delay, and a double-order WALTZ16 decoupling scheme (Zhou, Z. et al., J. Mag. Reson. 187 (2007) 225, and Busico, V. et al., Macromol. Rapid Commun. 2007, 28, 1128). A total of 6144 (6k) transient values ​​were collected for each spectrum. For quantitative 13 C{ 1H} NMR spectra are processed, integrated and the relevant quantitative properties are determined from the integral. All chemical shifts are indirectly referenced to the central methylene of the ethylene block (EEE) at 30.00 ppm using the chemical shift of the solvent. This method allows for comparable references even if this structural unit is not present. Characteristic signals corresponding to ethylene incorporation are observed (Cheng, HN, Macromolecules 17 (1984), 1950), and the comonomer fraction is calculated as the fraction of ethylene in the polymer relative to all monomers in the polymer: fE = (E / (P+E). The method of Wang et al. (Wang, WJ., Zhu, S., Macromolecules 33 (2000), 1157) is used by integration 13 C{ 1 H} spectrum to quantify the comonomer fraction. This method was chosen because of its robustness and its ability to account for the presence of regional defects when necessary. The integration region was slightly adjusted to increase applicability over the entire range of comonomer contents encountered. For systems with very low ethylene content (where only isolated ethylene in the PPEPP sequence was observed), the method of Wang et al. was modified to reduce the impact of site integration that no longer exists. This method reduces the overestimation of the ethylene content of the system and is achieved by reducing the number of sites used to determine the absolute ethylene content to E = 0.5 (Sββ + Sβγ + Sβδ + 0.5 (Sαβ + Sαγ)). By using this set of sites, using the same symbols as used in the literature by Wang et al. (Wang, WJ., Zhu, S., Macromolecules 33 (2000), 1157), the corresponding integral equation becomes E = 0.5 (I H +I G +0.5(I C +I D )). The equation for absolute propylene content was not modified. The mole percent of comonomer incorporation was calculated from the mole fraction: E [mol %] = 100 x fE. The weight percent of comonomer incorporation was calculated from the mole fraction: E [wt %] = 100 x (fE x 28.06) / ((fE x 28.06) + ((1 - fE) x 42.08)).

[0115] f) Talc and chalk content

[0116] TGA was determined according to the following procedure:

[0117] Thermogravimetric Analysis (TGA) experiments were performed using a Perkin Elmer TGA8000. About 10-20 mg of material was placed in a platinum pan. The temperature was equilibrated at 50°C for 10 minutes and then raised to 950°C at a heating rate of 20°C / min under nitrogen. The weight loss (WCO2) between about 550°C and 700°C was attributed to CO2 released from CaCO3, so the chalk content was estimated as:

[0118] Chalk content = 100 / 44×WCO2

[0119] The temperature was then lowered to 300°C at a cooling rate of 20°C / min. The gas was then switched to oxygen and the temperature was raised to 900°C again. The weight loss in this step is attributed to carbon black (Wcb). Knowing the contents of carbon black and chalk, the ash content excluding chalk and carbon black was calculated as follows:

[0120] Ash content = (ash residue) – 56 / 44 × WCO2 – Wcb

[0121] The ash content is the weight percentage measured in the first step carried out under nitrogen at 900° C. The ash content is estimated to be the same as the talc content of the regenerant studied.

[0122] g) MFR

[0123] The melt flow rate is measured at 230°C (polypropylene) and 190°C (polyethylene) under a load of 2.16 kg (MFR2). The melt flow rate is the number of grams of polymer extruded in 10 minutes at a temperature of 230°C and 190°C under a load of 2.16 kg according to ISO 1133 standardized test equipment.

[0124] h) Melting temperature

[0125] The melting temperature was measured using DSC according to ISO 11357-3 using a temperature gradient of 10°C / min.

[0126] i) Amount of metal

[0127] The amount of metal was determined by X-ray fluorescence (XRF).

[0128] j) Amount of paper and wood

[0129] Paper and wood were tested by common laboratory methods including grinding, flotation, microscopy and thermogravimetric analysis (TGA).

[0130] k) Limonene measurement

[0131] Limonene quantification was performed by standard addition using solid phase microextraction (HS-SPME-GC-MS).

[0132] 50 mg of ground sample was weighed into a 20 mL headspace vial and the vial was closed with a magnetic cap lined with silicone / PTFE after adding different concentrations of limonene and a glass coated magnetic stir bar. Diluted limonene standards of known concentrations were added to the sample using a microcapillary (10 pL). 0, 2, 20 and 100 ng were added, equivalent to 0 mg / kg, 0.1 mg / kg, 1 mg / kg and 5 mg / kg of limonene, in addition to standard amounts of 6.6 mg / kg, 11 mg / kg and 16.5 mg / kg of limonene were used in combination with some of the samples tested in this application. For quantification, ion 93 collected in SIM mode was used. Enrichment of the volatile fraction was performed by headspace solid phase microextraction for 20 minutes at 60°C with a 2 cm stable curved 50 / 30 pm DVB / Carboxen / PDMS fiber. Desorption was performed directly in the heated injection port of the GCMS system at 270°C.

[0133] GCMS parameters:

[0134] Column: 30m HP 5MS 0.25×0.25

[0135] Syringe: Splitless, with 0.75 mm SPME liner, 270 °C

[0136] Temperature program: -10℃ (1 minute)

[0137] Carrier gas: Helium 5.0, linear velocity of 31 cm / s, constant flow

[0138] MS: Single quadrupole, direct interface, 280°C interface temperature

[0139] Acquisition: SIM scan mode

[0140] Scan parameters: 20-300amu

[0141] SIM parameters: m / Z93, 100 ms dwell time

[0142] I) Total free fatty acid content

[0143] Fatty acid quantification was performed using headspace solid phase microextraction (HS-SPME-GC-MS) by standard addition.

[0144] 50 mg of ground sample was weighed into a 20 mL headspace vial and the vial was closed with a magnetic cap lined with silicone / PTFE after adding different concentrations of limonene and a glass coated magnetic stir bar. A known concentration of a diluted free fatty acid mixture (acetic acid, propionic acid, butyric acid, valeric acid, caproic acid and octanoic acid) standard was added to the sample at three different levels using a 10 μL microcapillary. 0, 50, 100 and 500 ng were added to equal 0 mg / kg, 1 mg / kg, 2 mg / kg and 10 mg / kg of each acid. For quantification, ion 60 collected in SIM mode was used for all acids except propionic acid, where ion 74 was used.

[0145] GCMS parameters:

[0146] Column: 20m ZB Wax plus 0.25×0.25

[0147] Syringe: Split 5:1, with glass lined split liner, 250°C

[0148] Temperature program: 40°C (1 min) at 6°C / min to 120°C, at 15°C to 245°C (5 min) Carrier gas: Helium 5.0, linear velocity of 40 cm / s, constant flow

[0149] MS: Single quadrupole, direct interface, 220°C interface temperature

[0150] Acquisition: SIM scan mode

[0151] Scan parameters: 46-250amu 6.6scans / s

[0152] SIM parameters: m / z 60, 74, 6.6 scans / s

[0153] experiment

[0154] The commercially available melt flow rate (ISO 1133, 230°C, 2.16 kg) was 0.25 g / 10 min, the tensile modulus was 1006 MPa (ISO 527-2), and the Charpy impact strength was 13 kJ / m 2 (ISO179-1) and a common random polypropylene copolymer (propylene ethylene copolymer) having an ethylene content of 4.5 wt% as component (C).

[0155] As component (B), a C2-C8 plastomer (Queo 6201, commercially available from Borealis) having a melt flow rate (ISO 1133, 190°C, 2.16 kg) of 1.0 g / 10 min, a melting temperature of 49°C and a tensile modulus of 4 MPa was used.

[0156] For blend (A), an experimental grade originating from household waste with a melt flow rate of 13.2 g / 10 min was used.

[0157] Table 1 shows the properties of the polypropylene / polyethylene blends (A) used for evaluation.

[0158] Table 1: Properties of Polypropylene / Polyethylene Blends (Blends Mixtures) (Blend A)

[0159]

[0160] The composition was compounded in a co-rotating twin-screw extruder Coperion ZSK 47 at 220°C with 0.15 wt% of an antioxidant (Irganox B215FF from BASF AG, Germany; Irganox B215FF is a 1:2 mixture of pentaerythritol-tetrakis(3-(3',5'-di-tert-butyl-4-hydroxyphenyl)-propionate (CAS No.: 6683-19-8) and tris(2,4-di-tert-butylphenyl) phosphite (CAS No.: 31570-04-4)).

[0161] Table 2: Experimental results

[0162]

[0163]

[0164] *ASTM D638-T4

[0165]

[0166] *ASTM D638-T4

[0167] It can be seen that the loss of stiffness caused by the addition of the C2C8 plastomers (which have a very low tensile modulus) is surprisingly very small. However, component (C), the random polypropylene copolymer, produces a surprising enhancement in terms of impact properties.

[0168] When CE4 (with a total of 20 wt% of the original material, the tensile modulus was 841 MPa and the impact strength was 28 kJ / m 2 ) and IE1 (also with a total of 20 wt% of virgin material, and a tensile modulus of 899 MPa, 15 kJ / m 2When comparing CE5 (30 wt% of virgin material) with IE8 (also with 30 wt% of virgin material), it can be seen that the stiffness is improved with only a very small deterioration and the impact is good (within acceptable limits). Furthermore, the low temperature impact strength data show quite small differences. Thus, the present invention allows avoiding undesirably low stiffness while still having reasonable impact performance. This is confirmed when comparing CE5 (30 wt% of virgin material) with IE8 (also with 30 wt% of virgin material): the stiffness of IE8 is much better.

[0169] It can also be seen that the addition of higher amounts of component (B) can improve the impact properties far beyond what is actually needed for common uses, while having less good stiffness.

Claims

1. A polyethylene-polypropylene composition having a melt flow rate of 5.0 to 12.0 g / 10 min measured at 230°C and 2.16 kg load according to ISO 1133, the polyethylene-polypropylene composition being obtained by blending: a) 52 to 92 wt% of a blend A, based on the total weight of the polyethylene-polypropylene composition, comprising: A-1) Polypropylene, and A-2) Polyethylene, wherein the weight ratio of polypropylene to polyethylene is from 19:1 to 7:3, and Blend A is a recycled material, which is recovered from waste plastic materials derived from post-consumer waste and / or industrial waste; b) based on the total weight of the polyethylene-polypropylene composition, 5 to 35 wt% of a compatibilizer B, wherein the compatibilizer B is selected from a C2C4 plastomer, a C2C6 plastomer, a C2C8 plastomer and a mixture thereof, and the compatibilizer B has: - a DSC melting point below 75°C measured according to ISO 11357; - MFR2 less than 1.5 g / 10min measured at 190°C and 2.16 kg load according to ISO1133; and - 885 kg / m2 measured according to ISO1183 3 The density below; c) 3 to 12 wt% of a random polypropylene copolymer, based on the total weight of the polyethylene-polypropylene composition, wherein the random polypropylene copolymer has an MFR2 of less than 1.0 g / 10 min measured at 230°C and 2.16 kg load according to ISO 1133; and d) 0 to 1.0 wt% of a stabilizer or a mixture of stabilizers, based on the total weight of the polyethylene-polypropylene composition, The polyethylene-polypropylene composition has a tensile modulus of at least 600 MPa measured according to ISO 527-2.

2. The polyethylene-polypropylene composition of claim 1, having a tensile modulus of at least 700 MPa measured according to ISO 527-2.

3. The polyethylene-polypropylene composition of claim 1, having a tensile modulus of at least 800 MPa as measured according to ISO 527-2.

4. The polyethylene-polypropylene composition of claim 1, wherein the polyethylene-polypropylene composition has a tensile modulus of 850 to 1000 MPa as measured according to ISO527-2.

5. The polyethylene-polypropylene composition of claim 1, wherein the polyethylene-polypropylene composition has a melt flow rate of 5.0 to 12.0 g / 10 min measured at 230°C and 2.16 kg load according to ISO 1133, and the polyethylene-polypropylene composition is obtained by blending: a) 71 to 89 wt% of a blend A, based on the total weight of the polyethylene-polypropylene composition, comprising: A-1) Polypropylene, and A-2) Polyethylene, wherein the weight ratio of polypropylene to polyethylene is from 19:1 to 7:3, and Blend A is a recycled material, which is recovered from waste plastic materials derived from post-consumer waste and / or industrial waste; b) based on the total weight of the polyethylene-polypropylene composition, 7 to 17 wt% of a compatibilizer B, wherein the compatibilizer B is selected from a C2C4 plastomer, a C2C6 plastomer, a C2C8 plastomer and a mixture thereof, and the compatibilizer B has: - a DSC melting point below 75°C measured according to ISO 11357; - MFR2 less than 1.5 g / 10min measured at 190°C and 2.16 kg load according to ISO1133; and - 885 kg / m2 measured according to ISO1183 3 The density below; c) 4 to 11 wt% of a random polypropylene copolymer, based on the total weight of the polyethylene-polypropylene composition, wherein the random polypropylene copolymer has an MFR2 of less than 1.0 g / 10 min measured at 230°C and 2.16 kg load according to ISO 1133; and d) 0 to 1.0 wt% of a stabilizer or a mixture of stabilizers, based on the total weight of the polyethylene-polypropylene composition, The polyethylene-polypropylene composition has a tensile modulus of 850 to 1000 MPa.

6. The polyethylene-polypropylene composition of claim 1, wherein the polyethylene-polypropylene composition has a melt flow rate of 5.0 to 12.0 g / 10 min measured at 230°C and 2.16 kg load according to ISO 1133, and the polyethylene-polypropylene composition is obtained by blending: a) 71 to 89 wt% of a blend A, based on the total weight of the polyethylene-polypropylene composition, comprising: A-1) Polypropylene, and A-2) Polyethylene, wherein the weight ratio of polypropylene to polyethylene is from 19:1 to 7:3, and Blend A is a recycled material, which is recovered from waste plastic materials derived from post-consumer waste and / or industrial waste; b) 7 to 17 wt% of a compatibilizer B, based on the total weight of the polyethylene-polypropylene composition, wherein the compatibilizer B is a C2C8 plastomer and has: - a DSC melting point below 75°C measured according to ISO 11357; - MFR2 less than 1.5 g / 10min measured at 190°C and 2.16 kg load according to ISO1133; and - 885 kg / m2 measured according to ISO1183 3 The density below; c) 4 to 11 wt% of a random polypropylene copolymer, based on the total weight of the polyethylene-polypropylene composition, wherein the random polypropylene copolymer has an MFR2 of less than 1.0 g / 10 min measured at 230°C and 2.16 kg load according to ISO 1133; and d) 0 to 1.0 wt% of a stabilizer or a mixture of stabilizers, based on the total weight of the polyethylene-polypropylene composition, The polyethylene-polypropylene composition has a tensile modulus of 850 to 1000 MPa.

7. The polyethylene-polypropylene composition according to any one of claims 1 to 6, wherein The DSC melting point of the compatibilizer B measured using DSC according to ISO 11357-3 using a temperature gradient of 10° C. / min is 73° C. or less.

8. The polyethylene-polypropylene composition according to any one of claims 1 to 6, wherein The density of the compatibilizer B measured according to ISO1183 is 875 kg / m 3 the following.

9. The polyethylene-polypropylene composition according to any one of claims 1 to 6, wherein Blend A has one or more of the following: (i) a limonene content of 0.1 ppm to 100 ppm, the limonene content being determined using solid phase microextraction HS-SPME-GC-MS; (ii) a polystyrene content of up to 6.0 wt %; (iii) a talc content of up to 3 wt%; (iv) a polyamide content of up to 5.0 wt %; (v) a chalk content of up to 1.0 wt %; (vi) a fatty acid content of 0.1 to 100 ppm, as determined using solid phase microextraction (HS-SPME)-GC-MS.

10. The polyethylene-polypropylene composition according to any one of claims 1 to 6, wherein The random polypropylene copolymer has an ethylene content of 3.0 to 6.0 wt%.

11. The polyethylene-polypropylene composition according to any one of claims 1 to 6, wherein The amounts of components a) to d) add up to 100 wt %.

12. An article comprising the polyethylene-polypropylene composition according to any one of claims 1 to 11.

13. A method for producing a polyethylene-polypropylene composition as claimed in any one of claims 1 to 11, comprising the steps of: a) providing a blend A in an amount of 52 to 92 wt%, based on the total weight of the polyethylene-polypropylene composition, wherein the blend A comprises polypropylene and polyethylene in a ratio of 19:1 to 7:3, wherein blend A is a recycled material, and the recycled material is recovered from waste plastic materials derived from post-consumer waste and / or industrial waste; b) providing a compatibilizer B in an amount of 5 to 35 wt% based on the total weight of the polyethylene-polypropylene composition, wherein the compatibilizer B is selected from a C2C4 plastomer, a C2C6 plastomer or a C2C8 plastomer, and the compatibilizer B has: - a DSC melting point below 75°C measured according to ISO 11357; - MFR2 less than 1.5 g / 10min measured at 190°C and 2.16 kg load according to ISO1133; and - 885 kg / m2 measured according to ISO1183 3 The density below; c) providing a random polypropylene copolymer in an amount of 3 to 12 wt% relative to the total weight of the polyethylene-polypropylene composition, wherein the random polypropylene copolymer has an MFR2 of 1.0 g / 10 min or less measured at 230°C and 2.16 kg load according to ISO 1133; d) melting and mixing the blend in the presence of 0 to 1.0 wt% of a stabilizer or a mixture of stabilizers relative to the total weight of the polyethylene-polypropylene composition; and e) Optional granulation.

14. Use of compatibilizer B and random polypropylene copolymer C and blend A for simultaneously obtaining at least 14 kJ / m 2 The invention relates to a method of manufacturing a composite material having a notched Charpy impact strength of at least 850 MPa and a tensile modulus of at least 850 to 1000 MPa in MPa, wherein the notched Charpy impact strength is measured non-instrumented at +23°C according to ISO 179-1 1eA, and the tensile modulus is measured according to ISO 527-2, wherein the compatibilizer B is a C2C8 plastomer and has: - a DSC melting point below 75°C measured according to ISO 11357; - MFR2 less than 1.5 g / 10min measured at 190°C and 2.16 kg load according to ISO1133; and - 885 kg / m2 measured according to ISO1183 3 The following densities, and The random polypropylene copolymer has an MFR2 of less than 1.0 g / 10 min measured at 230° C. and 2.16 kg load according to ISO 1133; The blend A comprises: A-1) Polypropylene, and A-2) Polyethylene, wherein the weight ratio of polypropylene to polyethylene is from 19:1 to 7:3, and Blend A is a recycled material recovered from waste plastic materials derived from post-consumer waste and / or industrial waste; and Blend A is present in an amount of 52 to 92 wt % relative to the final polyethylene-polypropylene composition, and The compatibilizer B is present in an amount of 5 to 35 wt % relative to the final polyethylene-polypropylene composition, and The random polypropylene copolymer is present in an amount of 3 to 12 wt% relative to the final polyethylene-polypropylene composition, the random polypropylene copolymer having an MFR2 of less than 1.0 g / 10 min measured according to ISO 1133 at 230°C and 2.16 kg load.